Developing Students' Ability In Writing Descriptive Text: A Case Study In Sma Negeri 1 Wonosari - Chusna, Yosi Mareta Mutia, Mauly Halwat Hikmat, Ph. D (2016)
The objectives of this study are to describe classroom procedures, teachers' techniques, problems faced and teacher's solutions of teaching writing descriptive text at SMA Negeri 1 Wonosari. This research uses descriptive qualitative research. The techniques for collecting data used in this study are observation, interviews, and documentation. The data of this research is information elicited from the students and teacher concerning classroom procedures and the techniques used by English teacher of SMA N 1 Wonosari. The writer also obtained data from the English teacher and students regarding problems faced and teacher's solutions of teaching writing descriptive text. The subject of this research is English teacher and students of A and B class. This research used data reduction, data display, and conclusion drawing and verification to analize the data. The findings of this study shows that the teacher used classroom procedures based on School-Based Curriculum: opening, main activities (exploration-elaboration-confirmation), and closing. The techniques used by the teacher are describing the picture, feedback, real objects, memorizing, translating, grouping, and correcting. The problems faced in teaching writing descriptive text are problem in developing idea, organizing idea, difficulties in vocabulary, tenses, and grammar, different capability of the students, and limited time. The solutions of English teacher's problems are: give material clearly, give simple assignment, repeat the previous materials, and used mix language. Keywords: classroom procedures, teacher's technique, problem faced and solution, writing class.